Smoking Pattern in Students of a Selected Medical College in Bangladesh (Journal of Enam Medical College, 2016)
Background: Smoking is a recognized harmful factor for general health. The prevalence of smoking is gradually increasing among the young people. Medical students are also vulnerable in this arena. Worldwide studies revealed that students start and continue smoking during their school and college periods.Objectives: To determine the current tobacco use among medical college students and to find out the risk factors associated with smoking and also to assess the knowledge of students regarding smoking.Materials and Methods: This cross-sectional study was conducted among medical students of different educational levels (first year to fifth year) in Enam Medical College, Savar, Dhaka during the period January to March 2012. An anonymous, pretested, selfadministered study questionnaire was distributed among the subjects. Data collected included smoking habits, demographic factors such as age, gender, parents occupation and monthly income. Study subjects were categorized as smokers, non-smokers and ex-smokers. Smoking-related knowledge was assessed and opinion regarding cessation of smoking was documented. The data were entered into the computer and statistical analyses were done using GraphPad Prism version 6.01.Results: Among the study subjects 290 were male and 202 were female. There were 79 (27.24%) smokers, 199 (68.62%) non-smokers and 12 (4.13%) ex-smokers among male and 197 (97.52%) non-smokers, 4 (1.98%) smokers and 1 (0.49%) ex-smoker in female. Regarding age, 196 (39.83%) students were below 20 years of age and 296 (60.16%) were more than 20 years of age. Most of the smokers (43.37%) are from affluent families. Influence of friends (44.57%) is the major reason of smoking followed by depression (27.71%). About 37.34% smokers have family members who are currently smoking. Regarding quitting smoking, 66% intended to stop smoking. The reasons for no intention to stop smoking include lack of incentive followed by addiction. There are significant differences among study subjects regarding smoking related knowledge.Conclusion: Even medical students are not fully aware of health consequences due to smoking and this lack of knowledge may lead to increase the number of smokers among students. Appropriate anti-smoking measures should be taken to create awareness about smoking and its health consequences and to reduce the incidence of smoking among the students.J Enam Med Col 2016; 6(3): 152-156